Style Characteristics of Individuality and Professional Competence of the Judge - Сергей Борисович Целиковский; Виктория Владимировна Гультяева (Российский психологический журнал, 2015)
The article considers diRerent approaches to the deSnition of the concept of “professional competence of the judge”. The authors have analyzed the relationship between the concepts of “acmeological invariants of professionalism” and “professionally important qualities”. They show the interrelation between acmeological invariants of professionalism and style characteristics of individuality. They also emphasize a system forming function of individual style characteristics of the subject. The analysis of psychological studies of professional activities of judges shows that the majority of them – being guided by ideas about its multifunctionality and multidimensionality, on the one hand, and high psycho-emotional tension, responsibility, social value, on the other – formulate extensive requirements to individual psychological qualities of the judge. Various authors emphasize such qualities of the judge as, for example, self-control, emotional restraint, ability to remain calm in stressful situations, exactingness to forms of behavior and statements of the participants, and also point to the importance of tolerance, tactfulness, ability to reduce excessive tenseness during the trial, emotional excitement of its participants. The stated requirements often overlap each other, diRer signiScantly in terms of their extent; they are heterogeneous from the point of view of fundamental models of mental individuality. A hidden idea of a static nature of the complex of “professionally important qualities” of a candidate, and hence fatality for his / her professional future, is an important shortcoming of these registers. Thus, the contradiction with the concepts of the formation of an individual style of activity in labour psychology and formation and development of professional subjectivity in acmeology is obvious. On the basis of the carried out comparative analysis of diRerent approaches to personal and behavioral characteristics of judges, the authors have made a conclusion about advantages of the oRered style approach to the study of individual psychological preconditions of professional competence of judges. In their opinion, assessment of style characteristics of personality is not so much a Sxation of its actual state as deSnition of possible directions of its further development, including the professional sphere.